Further evidence of the cross-reactivity of the Binax NOW® Filariasis ICT cards to non-Wuchereria bancrofti filariae: experimental studies with Loa loa and Onchocerca ochengi. Issue 1 (December 2016) - Wanji, Samuel; Amvongo-Adjia, Nathalie; Njouendou, Abdel; Kengne-Ouafo, Jonas; Ndongmo, Winston; Fombad, Fanny; Koudou, Benjamin; Enyong, Peter; Bockarie, Moses
Abstract Background The immunochromatographic test (ICT) for lymphatic filariasis is a serological test designed for unequivocal detection of circulatingWuchereria bancrofti antigen. It was validated and promoted by WHO as the primary diagnostic tool for mapping and impact monitoring for disease elimination following interventions. The initial tests for specificity and sensitivity were based on samples collected in areas free of loiasis and the results suggested a near 100 % specificity forW. bancrofti . The possibility of cross-reactivity with non-Wuchereria bancrofti antigens was not investigated until recently, when false positive results were observed in three independent studies carried out in Central Africa. Associations were demonstrated between ICT positivity andLoa loa microfilaraemia, but it was not clearly established if these false positive results were due toL. loa or can be extended to other filarial nematodes. This study brought further evidences of the cross-reactivity of ICT card withL. loa andOnchocerca ochengi (related toO. volvulus parasite) using in vivo and in vitro systems. Methods Two filarial/host experimental systems (L. loa -baboon andO. ochengi- cattle) and the in vitro maintenance of different stages (microfilariae, infective larvae and adult worm) of the two filariae were used in three experiments per filarial species. First, whole blood and sera samples were prepared from venous blood of patent baboons and cattle, and applied on ICT cards to detect circulating filarial antigens. Secondly, larval stages ofL. loa andO. ochengi as well asO. ochengi adult males were maintained in vitro. Culture supernatants were collected and applied on ICT cards after 6, 12 and 24 h of in vitro maintenance. Finally, total worm extracts (TWE) were prepared usingL. loa microfilariae (Mf) andO. ochengi microfilariae, infective larvae and adult male worms. TWE were also tested on ICT cards. For each experiment, control assays (whole blood and sera from uninfected babon/cattle, culture medium and extraction buffer) were performed. Results Positive ICT results were obtained with whole blood and sera ofL. loa microfilaremic baboons, culture supernatants ofL. loa Mf and infective larvae as well as withL. loa Mf protein extracts. In contrast, negative ICT results were observed with whole blood and sera from theO. ochengi- cattle system. Surprisingly, culture supernatant ofO. ochengi adult males and total worm extracts (Mf, infective larvae and adult worm) were positive to the test. Conclusions This study has provided further evidence ofL. loa cross-reactivity for the ICT card. All stages ofL. loa seem capable of inducing the cross-reactivity.Onchocerca ochengi. can also induce cross-reactivity in vitro, but this is less likely in vivo due to the location of parasite. The availability of the parasite proteins in the blood stream determines the magnitude of the cross-reactivity. The cross-reactivity of the ICT card to these non-W. bancrofti filariae poses some doubts to the reliability and validity of the current map of LF of Central Africa that was generated using this diagnostic tool.